2013
DOI: 10.1002/bsl.2082
|View full text |Cite
|
Sign up to set email alerts
|

Witnesses' Blindness for their Own Facial Recognition Decisions: A Field Study

Abstract: In a field study, we examined choice blindness for eyewitnesses' facial recognition decisions. Seventy-one pedestrians were engaged in a conversation by two experimenters who pretended to be tourists in the center of a European city. After a short interval, pedestrians were asked to identify the two experimenters from separate simultaneous six-person photo lineups. Following each of the two forced-choice recognition decisions, they were confronted with their selection and asked to motivate their decision. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
5
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 42 publications
10
44
5
1
Order By: Relevance
“…The results for similarity concur with earlier findings [1], [26]. Others, however, reported an effect of similarity for a limited selection of stimuli [14] or for concurrent (but not retrospective) detection [16].…”
Section: Resultssupporting
confidence: 89%
“…The results for similarity concur with earlier findings [1], [26]. Others, however, reported an effect of similarity for a limited selection of stimuli [14] or for concurrent (but not retrospective) detection [16].…”
Section: Resultssupporting
confidence: 89%
“…This supports the idea that the memory trace for the original rating was still accessible and could be retrieved at will. These findings support earlier indications that blindness phenomena cannot be reduced to weak memory or forgetting (Sagana et al, 2013). Over and above when participants did change their ratings (53.4% of trials), the shift in the answers from the original sympathy ratings to the subsequently remembered sympathy estimates was independent of whether a manipulation was detected or not.…”
Section: Discussionsupporting
confidence: 92%
“…Indirect evidence for such link comes from a field study (Sagana et al, 2013) that examined choice blindness for eyewitnesses’ facial recognition decisions. Sagana et al (2013) reported that participants who made an accurate lineup decision were more likely to notice a covertly performed manipulation at the end of the experiment (i.e., retrospectively ) than participants who made an erroneous recognition decision. In other words, participants’ memory, as indicated by recognition accuracy, was associated with higher detection rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of jurors and potential jurors in several different countries indicate that they have limited knowledge of eyewitness factors, though the extent of their knowledge varies, depending on the nature of the questions asked [(11) (U.S.); (12) (U.S.); (13) (Canada); (14) (Scotland); (15) (Norway); (16) (Australia); (17) (UK); (18) (U.S.)]. Furthermore, in assessing accuracy, jurors generally rely on factors that are poor predictors of accuracy, such as eyewitness confidence at trial, memory for minor details, and consistency of eyewitness testimony.…”
Section: What the Principal Participants In Criminal Justice Systems mentioning
confidence: 99%